Repair of posterior medial meniscal root tears in the setting of Outerbridge III and IV cartilage damage. Issue 5 (31st May 2017) - Witherow, Andrew; Young, James; Myers, Peter
Objectives: Reporting the clinical outcomes of our cohort of patients who underwent arthroscopic transtibial posterior medial meniscal root tear repair (MMRTr) in those patients who had Outerbridge cartilage degeneration of III or IV. Methods: 29 consecutive patients with isolated MMRT underwent trans-tibial repair with all patients completing pre-operative scoring and 20 patients completing both pre and post-operative questionnaires. Of this there were 18 patients who had Outerbridge III or IV cartilage degeneration in the medial compartment at the time of surgery. Data was collected prospectively to include the Oxford Knee Score (OKS), the Lysholm Score (LS), the Tegner Activity Level Scale (TS) and International Knee Documentation Committee Score (IKDC). Results: In the 18 patient cohort there was a mean age at the time of surgery of 57.22 (range 40 – 71) years and the mean follow up period was 26.77 (7.2 – 94.53) months. There was statistically significant improvement across all scoring measures (OKS p = 5.94e-07, LS p = 2.40e-07, IKDC p = 4.17e-06 and TS p = 0.023) in this cohort. Conclusion: There was a significant improvement in the clinical outcomes of all patients who underwent MMRTr despite the presence of Outerbridge III or IV cartilage injury.